"Pseudo solid" nuclear spin echo study of poly(ethylene oxide) grafted on silica. Comparison with magic‐angle spinning technique results. (13th September 2016) - Tajouri, Tahar; Ben Mariem, Mohamed Aymen; Hommel, Hubert
Abstract: The polymer/solid interface of Poly (ethylene oxide) (PEO) grafted on silica is studied by 1 H NMR. For grafted polymers, the dipolar interaction is an important factor in the spin–spin relaxation process. For this purpose, the part of the dipolar interaction that is not averaged to zero by the motion is used. The "pseudo solid" spin echo can indeed give an estimation of the nonzero average dipolar interactions. The appropriate pulse sequence permits a standard measurement of the average dipolar spin coupling involved in the transverse magnetization relaxation. The influence of some major parameters such as molecular weights of the chains, grafting ratios, and temperatures on the relaxation and ultimately on the concentration is followed by "pseudo solid" spin echo. The magic‐angle spinning technique is also used. The sample rotation confirms by the narrowing of the central line and the appearance of side bands, the existence of a residual dipolar interaction which reveals the concentration of high monomer units at the surface. The study of the side bands permits to calculate the second moment as a function of temperature. A fair agreement is obtained by these two independent techniques: pseudo solid echo and magic‐angle spinning.